2014
DOI: 10.1016/j.dnarep.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of dormant origins to genome stability: From cell biology to human genetics

Abstract: The ability of a eukaryotic cell to precisely and accurately replicate its DNA is crucial to maintain genome stability. Here we describe our current understanding of the process by which origins are licensed for DNA replication and review recent work suggesting that fork stalling has exerted a strong selective pressure on the positioning of licensed origins. In light of this, we discuss the complex and disparate phenotypes observed in mouse models and humans patients that arise due to defects in replication li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 86 publications
4
101
0
Order By: Relevance
“…As stated above, loading of multiple DHs at many replication origins is a way to store large amounts of the inactive replicative helicase before DNA synthesis takes place (Alver et al 2014). Consistent with this notion, the DH is very stable even in the presence of high salt concentrations.…”
Section: Mcm2-7 Atp Hydrolysis Activities Of the Occm Dh And Cmgsupporting
confidence: 66%
“…As stated above, loading of multiple DHs at many replication origins is a way to store large amounts of the inactive replicative helicase before DNA synthesis takes place (Alver et al 2014). Consistent with this notion, the DH is very stable even in the presence of high salt concentrations.…”
Section: Mcm2-7 Atp Hydrolysis Activities Of the Occm Dh And Cmgsupporting
confidence: 66%
“…14,43 Some of the effects of reduced Mcm loading might also be rescued by dormant origins, also contributing to the moderate phenotype. 44 However, despite the dormant origin hypothesis, it has been shown that reduced Mcm loading can lead to genomic instability especially when cells face additional replicative stress. 45,46 Interestingly, overexpression of Cdh1 causes the opposite phenotype with lengthening of G1, delayed entry into S phase and massive overreplication of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogene-induced replication stress is thought to induce firing of dormant origins, which facilitates completion of genome duplication (58). However, the observed increase in origin firing by GOF p53 was concomitant to S phase entry of cells and was dependent on TADI of GOF p53, needed to upregulate cyclin A expression ( Figure 5D).…”
Section: Methodsmentioning
confidence: 96%